PERCEPTION OF FRUGAL INNOVATION PRACTICES AMONG EMPLOYEES IN PAKISTANI SMES - Moazzam Latif; Muhammad Irfan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aims to investigate the perception of employees regarding “frugal innovation” strategies in SMEs of Pakistan focusing on differences in demographic profile like age, gender, job roles and firm size, drawing on the sample of 305 respondents from different SMEs of Pakistan, and by employing Analysis of Variance (ANOVA) as the analytical approach, the study reveals compelling findings. For example, the study found, significant differences in perception of frugal innovation between male and female respondents, particularly in terms of frugal functionality and cost, highlighting the need for gender inclusive strategies in SMEs’ innovation efforts. Hence, Policymakers and practitioners should promote sustainable growth and competitiveness in the SME sector by developing targeted and efficient frugal innovation strategies that address the diverse perspectives and priorities of different groups within SMEs.